Mg/Al mixed oxides: Preparation, properties and catalytic activity in transesterification of rapeseed oil - Kutálek, Petr; Kocík, Jaroslav; Hájek, Martin; Smoláková, Lucie; Čapek, Libor (University of Pardubice, 2012)
This paper reviews the preparation, physicochemical properties and application of Mg/Al mixed oxides. Attention is focused on the activity of Mg/Al mixed oxides in transesterification of rapeseed oil. The mixed oxides were prepared from hydrotalcites by calcination and were characterized by XRD, FTIR and AAS. The aim of work was to study the effect of Mg/Al mixed oxides properties such as Mg/Al mass ratio (2-4), the temperature of calcination (450-1000 °C), time of calcination (4-17 h) and post-treatment rehydration of mixed oxides on the activity of Mg/Al catalysts in the transesterification reaction. The results show that the highest catalytic activity was observed for Mg/Al catalysts with Mg/Al mass ratio of 3, calcination temperature of 450 °C, time of calcination of 8 hours and rehydration by water. The leaching of magnesium to liquid phase was also determined and was always less than 0.1 wt. % — the catalyst was stable.